Low-pressure thin-film composite nanofiltration membranes with enhanced selectivity and antifouling property for effective dye/salt separation - Li, Juan; Gong, Ji-Lai; Fang, Si-Yuan; Cao, Wei-Cheng; Tang, Si-Qun; Qin, Meng; Zhou, Huai-Yang; Wang, Yu-Wen (Journal of colloid and interface science, 2023)
[Display omitted] •Thin selective skin layer was prepared using NGQDs and CD as the aqueous monomers.•Separation performance experiments of the membrane were performed at low pressure.•The addition of NGQDs significantly elevated the rejection for small molecular dye.•Excellent rejection obtained not only for larger molecular dye but for smaller dye.•The NGQDs-CD-MWCNTs-5 membrane exhibited superior antifouling property. For better sustainable resource recovery and elevating the separation efficiency of dye/salt mixture, it is essential to develop an appropriate nanofiltration membrane for the treatment of textile dyeing wastewater containing relatively smaller molecule dyes. In this work, a novel composite polyamide-polyester nanofiltration membrane was fabricated by tailoring amino functionalized quantum dots (NGQDs) and β-cyclodextrin (CD). An in-situ interfacial polymerization occurred between the synthesized NGQDs-CD and trimesoyl chloride (TMC) on the modified multi-carbon nanotubes (MWCNTs) substrate. The incorporation of NGQDs significantly elevated the rejection (increased by ∼ 45.08%) of the resultant membrane for small molecular dye (Methyl orange, MO) compared to the pristine CD membrane at low pressure (1.5 bar). The newly developed NGQDs-CD-MWCNTs membrane exhibited enhanced water permeability without compromising the dye rejection compared to the pure NGQDs membrane. The improved performance of the membrane was primarily attributed to the synergistic effect of functionalized NGQDs and the special hollow-bowl structure of CD. The optimal NGQDs-CD-MWCNTs-5 membrane expressed pure water permeability of 12.35 L m-2h−1 bar−1 at the pressure of 1.5 bar. Noteworthily, the NGQDs-CD-MWCNTs-5 membrane not only showed high rejection for the larger molecular dye of Congo Red (CR, 99.50%) but also for the smaller molecular dye of MO (96.01%) and Brilliant Green (BG, 95.60%) with the permeability of 8.81, 11.40, and 6.37 L m-2h−1 bar−1, respectively at low pressure (1.5 bar). The rejection of inorganic salts by the NGQDs-CD-MWCNTs-5 membrane was 17.20% for sodium chloride (NaCl), 14.30% for magnesium chloride (MgCl2), 24.63% for magnesium sulfate (MgSO4), and 54.58% for sodium sulfate (Na2SO4), respectively. The great rejection of dyes remained in the dye/salt binary mixed system (higher than 99% for BG and CR, <21% for NaCl). Importantly, the NGQDs-CD-MWCNTs-5 membrane exhibited favorable antifouling performance and potential good operation stability performance. Consequently, the fabricated NGQDs-CD-MWCNTs-5 membrane suggested a prospective application for the reuse of salts and water in textile wastewater treatment owing to the effective selective separation performance.